Youth Leisure in Cultural Space of Modern City: State and Prospects of Development - Baranov, Vladimir V. (2020)
The relevance of this article is the need to study the leisure sphere of modern youth, since free time is one of the important means of forming a young person's personality. The use of free time by young people is a kind of indicator of culture, the range of spiritual needs and interests of a particular personality of a young person. The aim of the study is to analyze the strategy of youth leisure in the cultural space of the modern city. Research methods: as a research method, we used the questionnaire method, which allows us to analyze in detail the main forms and dynamics of the development of modern youth’s leisure practices living in an urban environment. Results of the research: the article considers the problems and prospects of leisure strategies’ development of young people living in the city. The features of organizing youth leisure in the city are described. The preferences of young people in leisure activities are revealed. The degree of satisfaction of young people with forms of leisure is analyzed. The article considers the respondents' awareness of the work of institutions of the social and cultural sphere in organizing leisure activities for young people in the city. The reasons that prevent young people from spending leisure time in accordance with their needs are identified. Alternative forms of leisure activities are considered. The novelty and originality of the study lies in the fact that for the first time the reasons why young people do not have the opportunity to build their leisure strategy in accordance with their needs are investigated: external reasons (lack of places, disinterest of organizers, certain forms of leisure are unattractive or unprofitable for entrepreneurs); internal reasons (strong employment at work, lack of energy after work, laziness). The reasons for the lack of interaction of young people with leisure and cultural organizations (lack of time; ignorance of where to address on this issue; unwillingness of the organizers to change the situation that is, ignoring the position of young people) are determined. It is revealed that young people show little interest in leisure activities organized by the authorities, since they are formal in nature and do not correspond to the leisure preferences of young people. For the first time, the main strategies for leisure activities for young people living in the city (meetings with friends, relatives, walks, computer games, viewing content, relaxing in silence, and reading) were identified. The strategies of leisure activities that are used to a lesser extent (visiting the cinema, theater; active recreation (Cycling, skating, various sports); attending concerts, exhibitions, master classes; learning foreign languages) are considered. It is revealed that young people are not satisfied with the available leisure opportunities in the city. The reasons for discontent are determined (limited material resources in the city for interesting forms of leisure; lack of cultural and leisure institutions in the city that would meet the requirements of young people; limited choice of institutions where you can spend your free time). There is a gap between the needs of young people in the field of leisure and the activities of the city's youth policy Department, which conducts events according to its own plan, without taking into account the opinion of young people. Young people's knowledge about events is examined and the problem is determined about unawareness of cultural and entertainment events that are associated with the lack of interest of young people and lack of desire of the organizers of the Department of culture to find out what interests this age group. Alternative forms of leisure that young people would like to see in the urban environment, as well as take part in them, are identified (such as cinemas, theaters, restaurants; amusement parks, attractions, water parks, bowling; master classes, courses, exhibitions; interest clubs (language, discussion, computer); Bicycle rental, roller skates, Quad bikes, go-karts; paragliding school; industrial tourism). Practical significance: the data Obtained in this work can be used in social psychology, pedagogy, age psychology, as well as for further theoretical development of this issue.